Safety of One-Stage Atrioventricular Junction Ablation after Pacemaker Implantation for Left Bundle Branch Pacing - Perepeka, Eugene O.; Sikhnevych, Roman A. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Atrial fibrillation (AF) is one of the most common arrhythmias. Atrioventricular (AV) junction ablation combined with pacemaker implantation has become an accepted, effective strategy for the treatment of symptomatic tachysystolic AF resistant to drug therapy, especially in the elderly. Left bundle branch (LBB) pacing is a physiological alternative to right ventricular pacing. The aim. This study evaluated the effectiveness and safety of a one-stage application of the implantation system for LBB pacing and ablation of the AV junction. Materials and methods. For the period from January 2023 to February 2024, LBB pacing was applied in 8 patients at the National Amosov Institute of Cardiovascular Surgery in the context of treatment of chronic tachysystolic form of AF with subsequent ablation of the AV junction, as a strategy to control heart rate. Results. In all the patients, LBB pacing criteria were achieved: Qr or qR in V1 QRS complex morphology type during pacing (100%); St-V6RWPT interval < 80 ms (mean 75.8 ± 13.9 ms); the difference between the intervals St-V1RWPT – St-V6RWPT > 44 ms (mean 55.57 ± 10.09 ms). In 3 out of 8 patients (37%) it was possible to register LBB potential. Mean paced QRS width in the studied group was 130 ± 18.02 ms. The mean intraoperative LBB pacing threshold was 1.71 ± 0.39 V for 0.4 ms, the anodal pacing threshold was 3.25 ± 0.5 V for 0.4 ms (we could demonstrate it in 6 out of 8 patients [75%]). Intraoperative lead perforation through the interventricular septum could be observed in 2 out of 8 cases (25%), but after that it was possible to successfully reimplant the lead in the area of the LBB. In all the patients of the studied group, it was possible to successfully perform radiofrequency ablation of the AV junction with the aim of heart rate control in chronic tachysystolic AF. There was no endocardial lead dislodgement in the postoperative period in any of the patients. Conclusions. In the studied group, no complications and hemodynamic disturbances were observed in the acute postoperative period and during follow-up one week after the pacemaker implantation for LBB pacing and AV junction ablation. Intraoperative transseptal perforation of the endocardial lead did not complicate reimplantation of the lead in the LBB area. A single-stage pacemaker implantation for LBB pacing and AV junction ablation can significantly shorten the patient’s stay in a medical institution. The subject requires further research on a larger number of patients with long-term follow-up.